2024
DOI: 10.1037/tra0001266
|View full text |Cite
|
Sign up to set email alerts
|

Implications of language use in posttraumatic nightmares on psychological symptoms.

Abstract: Objective: The current study sought to understand how language use in posttrauma nightmare (PTNM) reports may be related to psychological symptoms over the course of treatment. Method: Multiple regression analyses were conducted to examine the relationship between language use in PTNMs and psychological symptoms. Specifically, cognitive processing words (CPW) and emotional tone (ET) measured in PTNMs were analyzed in their relationship to posttraumatic stress disorder (PTSD) and depression symptom severity, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…As ERRT is known to be effective in reducing the distress and frequency of nightmares, as well as the severity of PTSD, depression, and improving sleep quality (Davis & Wright, 2007), it is possible that these treatment outcomes may be related to the measurement of language in the rescription. Indeed, such research has recently been conducted and is currently undergoing review (Paquet et al, in press). A preliminary study found that language use related to cognitive processing words within nightmares was significantly correlated to PTSD and nightmare symptoms (Paquet et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…As ERRT is known to be effective in reducing the distress and frequency of nightmares, as well as the severity of PTSD, depression, and improving sleep quality (Davis & Wright, 2007), it is possible that these treatment outcomes may be related to the measurement of language in the rescription. Indeed, such research has recently been conducted and is currently undergoing review (Paquet et al, in press). A preliminary study found that language use related to cognitive processing words within nightmares was significantly correlated to PTSD and nightmare symptoms (Paquet et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, those who endorsed a higher severity of negative post‐trauma cognitions about the world at baseline had nightmare narratives that reflected higher levels of analytical thinking. It is difficult to understand why a greater degree of analytical thinking in PTNM is associated with more maladaptive post‐trauma cognitions, as previous studies found significantly lower levels of analytical thinking in PTNM relative to dreams in a nonclinical sample (Paquet et al, 2020a, 2022; Pennebaker et al, 2015). Theoretically, that would mean that a significantly more severe form of disturbed dreaming is associated with lower levels of analytical thinking.…”
Section: Discussionmentioning
confidence: 99%